The Origins of the Catalan Romanesque Art: Political Discourse in the Historiography Context - Dyadyunova, Natalya A. (Actual Problems of Theory and History of Art, 2022)
This article raises the issue of the origins of the 11th –12th-centuries Catalan Romanesque pictorial tradition. The purpose of this work was to demonstrate the specific features and complexity of this regional artistic tradition and, referring to the example of the historiographical discourse that developed in medieval studies of the last century and at the beginning of the 21st century, to consider the main theories of the origin of Catalan Romanesque painting. Based on the analyzed works, the author notes that the researchers’ attempt to establish continuity between the Catalan and any other medieval artistic tradition was often associated with the political agenda in Catalonia. In the course of the study, the author identifies three main theories that prevailed in the works devoted to establishing the authorship of Romanesque Catalan painting: the Lombard theory, the South French theory and the Roman theory. Despite the persistence of the Northern Italian theory to determine the origins of Catalan painters (Master of Pedret), today the increasing number of researchers disputes the connection of Catalan workshops with Lombardy and insist on the influence of Rome and Southern Italy on the Romanesque artistic tradition of Catalonia. According to the author, the tendency to associate the Catalan art school with the Roman-Cassinian circle of monuments is directly related to the current separatist sentiments in the region and the desire to demonstrate the uniqueness of its national tradition, which was the successor of the Early Christian Art. In this article, the research history of the Catalan Romanesque art will be presented time in accordance with the current socio-political context in Catalonia for the first.